Analisis Perubahan PDRB Provinsi Bali Berdasarkan Dampak yang Dialami Industri Pariwisata - Hendru, Hendru; Vincent, Vincent; Candy, Candy (Implementasi Manajemen & Kewirausahaan, 2021)
The study at hand was made in the aims to investigate, and correlate between the Gross Regional Product (GRP) of Bali with the effects of Covid-19 on the tour and travel industry. The data used in the study is based on secondary data procured from notable and trustworthy websites such as the Government Statistics Department (BPS) and publishes only found in Google Scholar and Emerald. The data was collected with a quantitative approach in mind resulting in most of the data being analytical data and statistics. The state of the industry of tour and travel represented by the ratio and number of rooms occupied during a given year shows a significant drop from the then 59,56% to 15,61% and number of visitors dropped immensely, close to 83% from the year before. The effect it had on Bali’s GRP is a reversal in economic growth from 252.138.88 to 224.214.11 billion rupiah.